2006
DOI: 10.1021/om060409i
|View full text |Cite
|
Sign up to set email alerts
|

Single-Electron Oxidation of Monomeric Copper(I) Alkyl Complexes:  Evidence for Reductive Elimination through Bimolecular Formation of Alkanes

Abstract: Monomeric Cu(I) alkyl complexes (NHC)Cu(R) (NHC ) N-heterocyclic carbene; R ) Me or Et) and (dtbpe)Cu(Me) (dtbpe ) 1,2-bis(di-tert-butylphosphino)ethane) have been prepared, isolated, and characterized. Single-electron oxidation of the Cu(I) alkyl complexes upon reaction with AgOTf to form putative Cu(II) intermediates of the type [(L)Cu(R)] + (L ) NHC or dtbpe, R ) Me or Et) results in the rapid production of (L)Cu(X) (X ) OTf) and R 2 . Experimental studies suggest that the reductive elimination of R 2 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…In our calculations we have found a strong ligand effect on the energies of ligand dissociation and CÀCu II homolysis. There are few theoretical studies of C À Cu II homolysis [84] and a ligand effect on bond dissociation energy has not previously been noted, although calculated ligand effects on single electron transfer involving copper complexes have been recently reported. [105] The mechanistic work described in this paper sets the stage for a subsequent detailed mechanistic analysis of our recently reported enantioselective Cu-catalyzed aminooxygenation of alkenes, which can open the door to a more detailed understanding of catalytic, enantioselective, Cu-catalyzed, alkene amination reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our calculations we have found a strong ligand effect on the energies of ligand dissociation and CÀCu II homolysis. There are few theoretical studies of C À Cu II homolysis [84] and a ligand effect on bond dissociation energy has not previously been noted, although calculated ligand effects on single electron transfer involving copper complexes have been recently reported. [105] The mechanistic work described in this paper sets the stage for a subsequent detailed mechanistic analysis of our recently reported enantioselective Cu-catalyzed aminooxygenation of alkenes, which can open the door to a more detailed understanding of catalytic, enantioselective, Cu-catalyzed, alkene amination reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Bond dissociation energies were used in this analysis be-cause the C À Cu homolysis transition states were difficult and in most cases impossible to locate. [83,84] The calculated aminocupration transition states TS-A (path A) and TS-B (path B) have distorted square-planar copper geometries (Figure 9). Spin density analysis of transi- www.chemeurj.org tion states TS-A and TS-B indicate the majority of spin density resides on Cu and little increase in nitrogen spin from ground state to transition state is observed.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…After stirring for 1 h, N,N 0 -dimethylimidazolium-2-carboxylate (43.5 mg, 0.31 mmol) was added and the mixture became colorless again. The reaction was stirred at rt for another 1 h Et 2 O (20 mL) was then added and the formed precipitate was filtered off, washed with copious amounts of Et 2 O, and dried in vacuo to give the product as a white solid (96 mg, 73% H,4.72;N,6.56. Found: C,31.14;H,4.70;N.…”
Section: 2mentioning
confidence: 99%
“…11 Naturally, we were interested 40 in combining both concepts for the development of a latent catalyst for the Huisgen cycloaddition. While screening different complexes, we observed that [(SIPr)CuCl] 12 (SIPr = N,imidazolin-2-ylidene) was the least reactive catalyst and we envisaged that we could take advantage of such a 45 low reactivity for the development of a latent catalyst for this transformation.…”
mentioning
confidence: 99%